EFFECTIVENESS OF DEEP BREATHING RELAXATION ON DEPRESSION AND QUALITY OF LIFE FOR ELDERLY HYPERTENSION - Yunita Sari; Eka Sutrisna; Husna Maulida; Tarisa (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Hypertension is disease chronic many​ experienced by the elderly age and can cause various problem physique and psychological , including depression and decline quality live . One of the intervention non-pharmacological methods that are easy , safe , and can be done in a way independent is technique deep breathing relaxation . Research This aim For analyze effectiveness deep breathing relaxation to level depression and quality living in the elderly hypertension . Research use design quasi-experimental with approachone-group pretest-posttest . Population study totaling 43 elderly people hypertension in Paya Punteut Village , Muara Dua District , Lhokseumawe City, with sample A total of 30 respondents were selected through technique purposive sampling . The instrument used is Geriatric Depression Scale (GDS) and World Health Organization Quality of Life-BREF (WHOQOL-BREF). Data analysis was performed using the Paired Sample t-test . The results of the study show that score depression experience decline from 4.90 to 3.27, while score quality life increase from 78.70 to 82.80 after intervention given . Statistical tests showed a significant difference before and after the intervention (p<0.001). Thus, deep breathing relaxation techniques are effective in reducing depression and improving quality of life in elderly hypertensive patients.